Optimalisasi Layanan Perpustakaan Berbasis SIPRUS Di Perpustakaan UIN Sunan Kalijaga Yogyakarta - Idzhari Rahman; Syifaun Nafisah (Central Library of Universitas Sebelas Maret, 2019)
Basically, library can provide fully information, and rather quickly in accordance with the needs of users. This research the optimization of the library information system through using the existed features, and hopefully, it can increase the service for the users. This research is using the qualitative approach method, and this is also field research. Based on the analysis of the results using the SDLC method, SIPRUS (Library Information System) is the library database collection of the State Islamic University of Sunan Kalijaga. This system uses MYSQL which means Open Resource-Based. SIPRUS has the same task to collect, process, conserve, refind the information, borrow and restore the book to the circulation section, and statistical functions to know the user's data, the library uses information technology to collect data as the library collection. In accordance with this analysis of the results, it can be said that OPAC is very helpful for users in searching for efficient and effective information.